Regarding the formation of theoretical, methodological, conceptual and theoretical foundations of defense resource management in the system of ensuring the military and economic security of the state - Semenenko, Oleh; Skurinevska, Lesia; Ostapets, Oleh; Tolok, Polina; Onofriichuk, Petro; Tarasov, Oleh (Social Development and Security, 2023)
Purpose: The purpose of the article is to determine the theoretical and practical features of the formation of theoretical, methodological, conceptual and theoretical foundations of defense resources management, as well as to clarify the main concepts and terms, common and distinctive aspects of research in this direction of research. Method: the main methods of research are methods of analysis and synthesis, methods of military economic theory, induction and deduction, as well as comparison, formalization, abstraction. Findings: The main results of the article: on the basis of the latest research, the main problems of the development of theoretical, methodological and conceptual-theoretical foundations of defense resources management in Ukraine are identified; the main directions of formation of theoretical, methodological, conceptual theoretical foundations of defense resources management were formed; the main principles of the formation of the principles of defense resources management in the system of ensuring the military and economic security of the state are determined; common and distinctive features of the theoretical, methodological and conceptual-theoretical foundations of defense resource management are revealed; the key elements of the conceptual and theoretical foundations of defense resources management were formed. Theoretical implications: the peculiarities of the formation of theoretical, methodological, conceptual and theoretical foundations of defense resource management in the system of ensuring the military and economic security of the state are disclosed. Paper type: theoretical, descriptive, methodical.